Maldives : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2012)
The Maldives has taken steps to lay down the foundations of an antimoney laundering and counterterrorist financing (AML/CFT) framework. This report summarizes the AML/CFT measures that were in place in the Maldives at the time of the onsite visit (October 17-28, 2010) and shortly thereafter. The report describes and analyzes these measures and offers recommendations on how to strengthen certain aspects of the AML/CFT system. It also assesses the Maldives' level of compliance with the Recommendations of the Financial Action Task Force (FATF).